1992
DOI: 10.1080/00071669208417469
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell strength: A relationship between the mechanism of failure and the ultrastructural organisation of the mammillary layer

Abstract: 1. Stress analysis using modern computer modelling techniques indicated that the shell should fail in tension as a result of the accumulation of stress at its inner most surface with the characteristic notched appearance of the mammillary layer providing the ideal crack initiation site. 2. Practical observations however indicated that crack initiation does not inevitably lead to catastrophic failure. This partly explains why previous attempts to predict shell failure from classical engineering theory underesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…The highest mean values of these indicators were found in the enriched cages. Bain (1992) in accordance with results of this study reported a thinning of the eggshell with an increasing number of laying hens per area unit. Leyendecker et al (2002) and Pistekova et al (2006), unlike other researchers, found no significant differences in eggshell strength between cages and deep litter.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The highest mean values of these indicators were found in the enriched cages. Bain (1992) in accordance with results of this study reported a thinning of the eggshell with an increasing number of laying hens per area unit. Leyendecker et al (2002) and Pistekova et al (2006), unlike other researchers, found no significant differences in eggshell strength between cages and deep litter.…”
Section: Discussionsupporting
confidence: 82%
“…This was to a certain extent caused by the uniform diets for all groups of birds under study because dietary levels of macro-and microelements significantly affect plasma mineral levels (Sooncharernying and Edwards 1989;Bain 1992;Petrovič et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…They tested whole hens' eggs, compressing them between rigid, parallel platens, which caused failure by propagation of cracks from the contact points. They calculated K c using a formula previously devised by one of the authors [6]. More recently Xiao et al reported similar values, of the order of 12.6 MPa p m, in a paper investigating the effect of dietary supplements on hen egg properties [7].…”
Section: Introductionmentioning
confidence: 53%
“…Just prior to oviposition the proteinaceous cuticle is deposited onto the outermost surface of this calcified structure. The total thickness of the completed eggshell is approximately 320 μm but the main load bearing part of the shell corresponds to the combined thicknesses of the palisade, vertical crystal layer and cuticle (Bain 1992). …”
Section: Industrial Contextmentioning
confidence: 99%